2018
DOI: 10.1016/j.fertnstert.2018.02.136
|View full text |Cite
|
Sign up to set email alerts
|

Use of emergency contraception among female young adult cancer survivors

Abstract: Female young adult cancer survivors were significantly more likely to use emergency contraception compared with the general population. Populations including nonwhite survivors have a higher risk, suggesting differences in family planning care. Strategies to improve contraception and decrease the need for emergency contraception are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
0
14
0
1
Order By: Relevance
“…For example, survivors who assume that they are at risk despite a fertility status that seems normal may become anxious about their family planning, which could result in unnecessary worry and distress and thus affect their emotional health. Also, such misperceptions could affect survivors' physical health if they have unplanned pregnancies, 11 increased use of emergency contraception, 56 and/or acquire sexually transmitted diseases secondary to engaging in unprotected sexual behaviors. In contrast, survivors with impaired fertility who perceive themselves at no increased risk also raise concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, survivors who assume that they are at risk despite a fertility status that seems normal may become anxious about their family planning, which could result in unnecessary worry and distress and thus affect their emotional health. Also, such misperceptions could affect survivors' physical health if they have unplanned pregnancies, 11 increased use of emergency contraception, 56 and/or acquire sexually transmitted diseases secondary to engaging in unprotected sexual behaviors. In contrast, survivors with impaired fertility who perceive themselves at no increased risk also raise concern.…”
Section: Discussionmentioning
confidence: 99%
“…15 This again underscores the importance of educating survivors about their reproductive health. 56,57 Addressing survivors' fertility status after treatment will continue to be a salient issue in the future. Although there are many efforts to increase fertility preservation at diagnosis, preservation is not viable for every patient or family, and preservation methods remain experimental for prepubertal patients.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in the literature, data suggest that they are less likely to receive adequate contraception counselling, with rates up to 56% of survivors reporting no family planning counselling at all (Castro-Sanchez et al, 2018). Additionally, they are less likely to be satisfied and compliant with the prescribed method (Blouet et al, 2019) and more likely to wrongly assume they are infertile and to face unwanted pregnancies (Medica et al, 2018;Hadnott et al, 2019). Information on contraception during chemotherapy, along with information on fertility preservation, is part of our pre-therapy counselling.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that cancer survivors are more likely to use emergency contraception than their peers (Medica et al, 2018), opening a debate on the best way to empower them with fertility awareness and enhancing the need for a multidisciplinary approach that includes the fertility specialist also during oncologic follow-up (Nahata and Quinn, 2018). Women who are not (or not yet) wishing for a pregnancy could benefit from a long-term follow-up for managing the gynecological adverse effects of anticancer therapies, counselling on contraception or menopause, or evaluation of their post-treatment ovarian reserve and reproductive potential.…”
Section: Introductionmentioning
confidence: 99%
“…Despite clinical guidelines recommending adequate contraception for survivors of cancers occurring in adolescence and young adulthood, contraception rates are lower and use of emergency contraception is higher in this population than in the general U.S. population of reproductive-age women (16)(17)(18)(19)(20). Moreover, studies have shown that cancer survivors also have lower utilization rates of highly effective contraceptive methods categorized as tier I (surgical sterilization, contraceptive implant, intrauterine device [IUD]) or II (combined hormonal contraceptive, injectable progestin, progestin-only pills, lactation amenorrhea) by the World Health Organization (WHO) (18).…”
mentioning
confidence: 99%